Minimal residual disease detected by droplet digital PCR in peripheral blood stem cell grafts has a prognostic impact on high-risk neuroblastoma patients. Issue 10 (October 2022) - Nino, Nanako; Ishida, Toshiaki; Nakatani, Naoko; Lin, Kyaw San; Win, Kaung Htet Nay; Mon, Cho Yee; Nishimura, Akihiro; Inoue, Shotaro; Tamura, Akihiro; Yamamoto, Nobuyuki; Uemura, Suguru; Saito, Atsuro; et al.
Abstracts: More than half of high-risk neuroblastoma (NB) patients have experienced relapse due to the activation of chemoresistant minimal residual disease (MRD) even though they are treated by high-dose chemotherapy with autologous peripheral blood stem cell (PBSC) transplantation. Although MRD in high-risk NB patients can be evaluated by quantitative PCR with several sets of neuroblastoma-associated mRNAs (NB-mRNAs), the prognostic significance of MRD in PBSC grafts (PBSC-MRD) is unclear. In the present study, we collected 20 PBSC grafts from 20 high-risk NB patients and evaluated PBSC-MRD detected by droplet digital PCR (ddPCR) with 7NB-mRNAs (CRMP1, DBH, DDC, GAP43, ISL1, PHOX2B, and TH mRNA). PBSC-MRD in 11 relapsed patients was significantly higher than that in 9 non-relapsed patients. Patients with a higher PBSC-MRD had a lower 3-year event-free survival (P = 0.0148). The present study suggests that PBSC-MRD detected by ddPCR with 7NB-mRNAs has a prognostic impact on high-risk NB patients. Abstract : Neuroblastoma (NB); Minimal residual disease (MRD); Peripheral blood stem cell (PBSC); Neuroblastoma-associated mRNAs (NB-mRNAs); Droplet digital PCR (ddPCR).